Change of Organizational Ambidexterity in Corporate Venture Units: how an Innovation Unit Increasingly Develops Exploitative Tendencies - Seilz, Veronika; Krause-Söhner, Elena; Schaller, Christian; Roth, Angela (HMD : Praxis der Wirtschaftsinformatik, 2023)
The ability to engage in organizational ambidexterity (OA), i.e., to simultaneously make innovative efforts (exploration) in addition to optimizing the existing business (exploitation), is crucial for the long-term success of companies. Separate corporate venture units (CVUs) are often founded for this purpose. They have a special role to play as they have to contribute to the ambidexterity of their parent companies and at the same time develop their own OA-configurations, i.e. combinations of exploration and exploitation. Previous research shows that these combinations change over time and that exploitation is increasing in originally explorative innovation units. However, there has been little insight into how the associated changes look like, what initiates them, and how they can be influenced. This study therefore addresses the following research question: Through what can exploitative and explorative tendencies develop in a CVU? Using a case study in a CVU of the paper processing industry, various examples can be used to show how the combinations of exploration and exploitation change over time at different levels and how these changes are influenced by the CVU and its members. Concluding management implications indicate that accompanying role changes and the individual attitudes of employees need to be guided by management. <br
Keywords: Ambidexterity; Innovation capability; Corporate venture unit; Dynamic perspective; Multi-level construct; Case study

Dynamics of Organizational Ambidexterity. Studies from a Processual Constructivist Perspective - Krause, Elena (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2021)
Keywords: Organizational Ambidexterity; Process; Change Management; Innovation; Exploration; Exploitation

Managing the Dynamics of Ambidexterity: A longitudinal case study of the European Envelope-Industry - Krause, Elena; Roth, Angela; Schaller, Christian; Möslein, Kathrin (2019 R&D Management Conference, 2019)

Multifaceted and even contradictory? Impulses to push efficiency and innovativeness and the dynamic role of ambiguity in context of a German university - Krause-Söhner, Elena; Roth, Angela; Schaller, Christian (Journal of Business Research, 2022)
Organizations have to find ideal combinations of efficient and innovative practices to manage the dynamic in changing contexts. However, we know less so far about managing the occurring dynamics of exploration–exploitation change and how they can be influenced. This study develops a novel dynamic and multi-level view on organizational ambidexterity (OA; i.e. the capacity to explore and exploit simultaneously). This view builds upon a processual constructivist perspective and the context of strategic change in a German Multi-campus university. In a longitudinal in-depth case study, organizational dynamics are investigated at multiple levels and sites. The results show that diverse—and somehow contradictory—impulses are operating on multiple levels and these are interpreted in different ways, leading to several organizational responses. The findings reveal the role of ambiguity, expressed along the categories of “identity conflicts”, “role confusion” and “sensegiving void”, in processing these impulses on multiple levels. This research contributes to the emerging discourse on dynamic ambidexterity by providing implications for managers seeking to manage the dynamics of ambidexterity change in public service sector.
CRIS-Team Scopus Importer:2022-04-29
Keywords: Case study; Dynamic ambidexterity; HEIs; Longitudinal; Theory development; Universities

Multi-level interaction effects during digital innovation activities: A case study from a digital innovation unit in the paper processing industry - Seilz, Veronika; Krause-Söhner, Elena; Schaller, Christian; Roth, Angela (BAM2023 Conference Proceedings, 2023)

Organizational ambidexterity from a process-oriented perspective: A systematic literature review - Krause, Elena; Roth, Angela; Schaller, Christian (European Academy of Management (EURAM) Annual Conference 2020 (Dublin, Ireland), 2020)
Keywords: process; ambidexterity; review

Role of change management in context of SAP-ERP system implementation - Krause, Elena (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2014)
Multi-Method-Study with Mayer-Kuvert-Network, Pfizer, Mägerle AG<br

Strategically influencing the multi-level dynamics of ambidexterity in academia – A longitudinal case study in a multi-campus university. - Krause, Elena (10th EURAM Early Career Colloquium (EECC), 2019)

Strategic ambidexterity development in a public service context: Changing the focus on short-term improvements and long-term innovation in a multi-campus university. - Krause, Elena; Roth, Angela; Schaller, Christian (European Academy of Management (EURAM) Annual Conference 2019, 2019)

The dynamics of organizational ambidexterity – An analysis about the role of organizational identity in strategic change - Krause, Elena (Doctoral Colloquium of the18th EURAM Conference, 2018)

Towards a model of ambidexterity change: A multi-level case study in a German multi-campus university - Krause, Elena; Roth, Angela; Schaller, Christian (BAM British Academy of Management Conference 2019, 2019)
Keywords: exploitation; exploration; dynamic; longitudinal; multi-level